Cone beam computed tomography in endodontics - Durack,Conor (2012)
Cone beam computed tomography (CBCT) is a contemporary, radiological imaging system designed specifically for use on the maxillo-facial skeleton. The system overcomes many of the limitations of conventional radiography by producing undistorted, three-dimensional images of the area under examination. These properties make this form of imaging particularly suitable for use in endodontics. The clinician can obtain an enhanced appreciation of the anatomy being assessed, leading to an improvement in the detection of endodontic disease and resulting in more effective treatment planning. In addition, CBCT operates with a significantly lower effective radiation dose when compared with conventional computed tomography (CT). The purpose of this paper is to review the current literature relating to the limitations and potential applications of CBCT in endodontic practice.